Simultaneous angiotensin receptor blockade and glucagon‐like peptide‐1 receptor activation ameliorate albuminuria in obese insulin‐resistant rats. (5th December 2019) - Rodriguez, Ruben; Escobedo, Benny; Lee, Andrew Y.; Thorwald, Max; Godoy‐Lugo, Jose A.; Nakano, Daisuke; Nishiyama, Akira; Parkes, David G.; Ortiz, Rudy M.
Abstract: Insulin resistance increases renal oxidant production by upregulating NADPH oxidase 4 (Nox4) expression contributing to oxidative damage and ultimately albuminuria. Inhibition of the renin‐angiotensin system (RAS) and activation of glucagon‐like peptide‐1 (GLP‐1) receptor signalling may reverse this effect. However, whether angiotensin receptor type 1 (AT1) blockade and GLP‐1 receptor activation improve oxidative damage and albuminuria through different mechanisms is not known. Using insulin‐resistant Otsuka Long‐Evans Tokushima Fatty (OLETF) rats, we tested the hypothesis that simultaneous blockade of AT1 and activation of GLP‐1r additively decrease oxidative damage and urinary albumin excretion (Ualb V) in the following groups: (a) untreated, lean LETO (n = 7), (b) untreated, obese OLETF (n = 9), (c) OLETF + angiotensin receptor blocker (ARB; 10 mg olmesartan/kg/d; n = 9), (d) OLETF + GLP‐1 mimetic (EXE; 10 µg exenatide/kg/d; n = 7) and (e) OLETF + ARB +exenatide (Combo; n = 6). Mean kidney Nox4 protein expression and nitrotyrosine (NT) levels were 30% and 46% greater, respectively, in OLETF compared with LETO. Conversely, Nox4 protein expression and NT were reduced to LETO levels in ARB and EXE, and Combo reduced Nox4, NT and 4‐hydroxy‐2‐nonenal levels by 21%, 27% and 27%, respectively. At baseline, Ualb V was nearly double in OLETF compared with LETO and increased to nearly 10‐fold greater levels by the end of the study. Whereas ARB (45%) and EXE (55%) individually reduced Ualb V, the combination completely ameliorated the albuminuria. Collectively, these data suggest that AT1 blockade and GLP‐1 receptor activation reduce renal oxidative damage similarly during insulin resistance, whereas targeting both signalling pathways provides added benefit in restoring and/or further ameliorating albuminuria in a model of diet‐induced obesity.